N019 Nurse-led video conference (VC) clinic follow-up of IBD patients in the remote and rural setting of the Scottish Highlands. (16th January 2018) - Armour, D; Fraser, M; Potts, L
Abstract: Background: The Highland region of Scotland has the highest prevalence of inflammatory bowel disease in the UK. NHS Highland covers an area of 25656 kg 2 geographically the largest health board in the UK. This provides logistic challenges to the provision of healthcare with more remote patients needing to travel for many hours by road, ferry and aircraft to reach specialist care. Our patient population is around 300000 with in excess of 1200 IBD patients. Our challenge is therefore to provide equity of care to all our patients, irrespective of geography. Our aim was to re-design our service to provide high quality, patient focused care in keeping with the UK National IBD standards. Whilst improving timely rapid access to specialist advice and assessment. Pressure on delivering healthcare continues to increase with a rising prevalence of IBD, greater patient expectations and development of new technologies and medications. There was a limited capacity in Raigmore Hospital to expand outpatient capacity. Most remote GP practices and smaller hospitals had video conference facilities. A dedicated VC room was established for use by the IBD team. Methods: IBD VC clinic of Advanced Nurses IBD data were recorded and reviewed between January 2016 and June 2017. Locations included both remote hospitals and GP practices. These locations being both the furthest North and West from specialist IBD care at Raigmore, Inverness. Travel times and distance was calculated between the patients home postcode and Raigmore hospital. The patients home postcode and VC clinic location. Time needed to travel from their home to the respective clinic—shortest and fastest route calculated using google map. Travel costs calculated based on NHS Highland rates of reimbursement and deducation for patient travel financial assistance. Eighty-eight patients were assessed having a total of 229 VC appointments. Clinic letters were accessed to identify pre-determined endpoints Results: Total patients 88; 52% male; mean age 48 years; 48% ulcerative colitis; 45% Crohns disease; 7% IBD unclassified. Travel distance, times and costs—mean distance from home to Raigmore 173.7 km; return 347.5 km; mean travel time to Raigmore 179 min; return 358 min; mean distance VC clinic from home 18.3 km; mean travel time to VC clinic 20.1 min; mean distance saved per appointment 310.9 km; mean time travelling saved per appointment 318 min; total appointments n = 229; total distance saved for all patients = 72245.3 km; total driving time saved for all patients = 1194.8 h; mean driving costs saved per appointment = £12.03 p; overall driving costs saved for 229 appointments £6284.78 p. Conclusions: (i) Nurse Led VC clinics are safe. (ii) Well-accepted by patients. (iii) Offer an excellent alternative to traditional follow-up models. (iv) Time and cost-effective.